An Alternative Fragmentation Pathway of 5H‐1, 4, 2‐Oxathiazoles Under Basic Conditions. Issue 26 (12th September 2017) - Yong, Fui Fong; Hewitt, Russell J.; Ong, Michelle J. H.; Qiu, Guanqi; Burkett, Brendan A.
Abstract: Recent advances in the synthesis of 1, 4, 2‐oxathiazoles have enabled unprecedented structural diversity to be achieved for this class of heterocycles, including 5H‐substituted derivatives. 1, 4, 2‐oxathiazoles have long been known to undergo fragmentation to afford isothiocyanates and carbonyl‐containing molecules under thermal conditions, yet the behavior of 5H‐1, 4, 2‐oxathiazoles has yet to be investigated. Based on literature reports, 5H‐1, 4, 2‐oxathiazoles would be expected to display similar behavior under thermal conditions as their 5, 5‐dialkyl/diaryl substituted cousins, but further chemistry of the 5H‐substituent has not been explored. In this preliminary report, the reactivity of 5H‐1, 4, 2‐oxathiazoles under basic conditions has been investigated, revealing an alternative fragmentation pathway whereby 5H‐1, 4, 2‐oxathiazoles produce nitriles and the corresponding thioacid salts. Significantly, the base promoted fragmentation pathway is able to be invoked at room temperature, allowing the reaction to proceed without generating any isothiocyanate. Abstract : A mild, base‐promoted fragmentation pathway of 5H‐1, 4, 2‐oxathiazoles is described. Optimal conditions involve treatment of the 5H‐1, 4, 2‐oxathiazoles with potassium carbonate in methanol at room temperature, followed by a solvent exchange with acetonitrile.